Climate change 2007 : the physical science basis : contribution of Working Group I to the Fourth Assessment Report of the Intergovernmental Panel on Climate Change (Cambridge University Press, 2020)
For policymakers -- Technical summary -- Historical overview of climate change science -- Changes in atmospheric constituents and radiative forcing -- Observations: atmospheric surface and climate change -- Observations: changes in snow, ice, and frozen ground -- Observations: ocean climate change and sea level -- Paleoclimate -- Coupling between changes in the climate system and biogeochemistry -- Climate models